Suicide and self-injurious behavior in children and adolescents (Research, Society and Development, 2020)
Introduction: both ideation, planning and attempted suicide, as well as self-injurious behaviors are issues of concern to public health worldwide. At this juncture, another aspect that deserves attention is the suicide rates among children and adolescents, which, according to research, self-annihilation is the second leading cause of death among adolescents. Objective: to discuss the issue of suicidal and parasuicidal attitudes among children and adolescents, their risk factors and peculiarities, in order to collaborate with their understanding and prevention. Method: a narrative bibliographic review was carried out with articles published in the last 7 years (2013-2020), using the databases National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO), Lilacs, Portal de Periódicos da Capes , Google Scholar and Psyinfo "suicide", "parasuicidal behavior", "self-injurious behavior", "parasuicide", "childhood", "adolescence", "suicide attempt", "childhood depression", "depression" were used as descriptors in adolescence ”,“ mental disorder in childhood ”, mental disorder in adolescence”, “self-aggressive behavior”, “puberty” and the Boolean “AND” or “E”. Results and discussion: both suicide and self-injurious behavior are much more frequent than official statistics demonstrate; this is because many suicide attempts are not reported or when they are, they do not follow the requirements of the official health and epidemiological surveillance agencies, which must be mandatory, immediate and at the municipal level, by any member of the health team. Conclusion: depression among other mental disorders are the main etiologies of suicidal and self-injurious behaviors in children and adolescents. There are factors that neglect and negatively influence the prognosis of these issues, such as the feelings of guilt, prejudice and stigma of family members and caregivers, who could have a sense of responsibility for the integral health of their pubescent and pre-pubertal entities.